1987
DOI: 10.1063/1.339256
|View full text |Cite
|
Sign up to set email alerts
|

Al-doped and Sb-doped polycrystalline silicon obtained by means of metal-induced crystallization

Abstract: Thin-film multilayer structures of a-Si/Al/a-Si and a-Si/Sb/a-Si were deposited by electron-beam evaporation. The microstructure and the electrical properties of as-deposited and annealed (T<1370 K) thin films were determined. A p-n junction was formed between polycrystalline silicon (poly-Si) doped with Sb and a p-type Si substrate. Al and Sb were found to induce crystallization of a-Si at 600 and 700 K, respectively. After annealing to 1370 K for 60 min, the resistivities 7.0×10−3 Ω cm for the Al-Si s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…It has been reported that a metal used for MIC will precipitate at the Si grain boundaries after annealing. 15 Figure 3 shows the calculated grain size from Scherrer's equation for a Si (1 1 1) or Ge (1 1 1) plane. Scherrer's equation is…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a metal used for MIC will precipitate at the Si grain boundaries after annealing. 15 Figure 3 shows the calculated grain size from Scherrer's equation for a Si (1 1 1) or Ge (1 1 1) plane. Scherrer's equation is…”
Section: Resultsmentioning
confidence: 99%
“…The process is known as metal induced crystallization (MIC) which lowers the crystallization temperature of amorphous semiconductors [5,6]. It has reported that the mechanisms of MIC are by the formation of metal silicides and the formation of eutectic alloys or by the combination of the two processes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Metal induced crystallization (MIC) of amorphous Si (a-Si) is a method for obtaining polycrystalline Si (poly-Si) of large grain sizes at low temperatures [1,2]. The effects caused by MIC of a-Si are widely studied and experimental knowledge has been accumulated [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%